Value Addition in Gemstones by Nuclear Techniques - Ahmad, Waqar; Mohiuddin, Fawad (The Nucleus, 2023)
Northern areas of Pakistan are rich in minerals and different types of precious/ semi-precious gemstones. One of these gemstones called topaz is quite abundant in Gilgit-Baltistan, Skardu and Kashmir regions. Although, topaz is a semi-precious stone but pink topaz from Mardan district in KPK province has a high worth in its natural form because it is rare in the world. In general, topaz is a colorless transparent stone, which is not very expensive. These semi-precious stones can be made precious by adding colors using different treatments like thermal heating, electron beam exposure, gamma rays or neutron irradiations. Except for electrons and neutrons, all other treatments give brown, golden or light blue colors, which are of low worth. The colors are usually not stable and fade away with the passage of time. About 30-40 times value can be added if the color is persistent dark blue. This deep blue color in topaz can be produced by neutron irradiation from a nuclear reactor. At present, for semi-precious stones, the world market is in the hands of blue topaz; typically named as Sky blue, Swiss blue and London blue. Countries like Indonesia, Thailand and US are already in this business and making significant profit. Pakistan Research Reactor (PARR-1) at the Pakistan Institute of Nuclear Science & technology (PINSTECH) has the capability to produce these desirable colors. Therefore, handsome revenue can be generated by utilizing this methodology. Apart from this, the other benefits are the development of a useful technology, collaboration between public and private sectors and application of nuclear techniques for peaceful purposes, which is one of the objectives of Pakistan Nuclear Society (PNS).